Numerical study of the effects of hydrodynamic interactions among cells for microfluidic holographic cyto-tomography - Vitolo, Angela; Villone, Massimiliano M.; Maffettone, Pier Luca (Frontiers in Physics, 2024)
If the cells contained in a suspension flowing along a microfluidic channel rotate while passing through the field of view (FOV) of a holographic microscope, they can be probed by a light beam from many different angles. From this, it is possible to retrieve the 3D refractive index map of each flowing cell, i.e., a 3D phase-contrast tomogram. To properly design microfluidic devices allowing to do that, it is important to understand the effects of the hydrodynamic interactions among cells on their in-flow rotation. Here, we investigate through direct numerical simulations the dynamics of clusters of cells suspended in a Newtonian liquid subjected to pressure-driven flow in a microfluidic channel with the aim of elucidating the effects of the hydrodynamic interactions on cell rotational behaviour and mechanical deformation.